2021
DOI: 10.5194/nhess-21-3407-2021
|View full text |Cite
|
Sign up to set email alerts
|

The mud volcanoes at Santa Barbara and Aragona (Sicily, Italy): a contribution to risk assessment

Abstract: Abstract. The Santa Barbara and Aragona areas are affected by mud volcanism (MV) phenomena, consisting of continuous or intermittent emission of mud, water, and gases. This activity could be interrupted by paroxysmal events, with an eruptive column composed mainly of clay material, water, and gases. They are the most hazardous phenomena, and today it is impossible to define the potential parameters for modelling the phenomenon. In 2017, two digital surface models (DSMs) were performed by drone in both areas, t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…The proposed method could be tested and validated on other application cases of volcano eruptions featuring different characteristics (such as the Maccalube of Aragona, where many more events and activity have been recorded in the last years [33] compared to those of Santa Barbara) or to other paroxysmal events to assess its capabilities. Another future research direction would be the extension of the current study to find heuristic criteria that are able to guide the choice of the three parameters characterizing the proposed methodology using information on the geology of the area, or according to specific problem classes (paroxysmal vs persistent events), or for specific application tasks (volcanic eruptions, landslides, subsidence, monitoring of buildings, etc.).…”
Section: Discussionmentioning
confidence: 99%
“…The proposed method could be tested and validated on other application cases of volcano eruptions featuring different characteristics (such as the Maccalube of Aragona, where many more events and activity have been recorded in the last years [33] compared to those of Santa Barbara) or to other paroxysmal events to assess its capabilities. Another future research direction would be the extension of the current study to find heuristic criteria that are able to guide the choice of the three parameters characterizing the proposed methodology using information on the geology of the area, or according to specific problem classes (paroxysmal vs persistent events), or for specific application tasks (volcanic eruptions, landslides, subsidence, monitoring of buildings, etc.).…”
Section: Discussionmentioning
confidence: 99%
“…The monitoring in such a framework could also serve as a warning system for the community in case of particularly intense eruptions. As a sad example, the mud volcano eruption occurred in 2014 at the Maccalube di Aragona (Agrigento, Sicily) caused the death of two children (e.g., Gattuso et al, 2021). The violent eruption of LUSI (Indonesia) mud volcano consisted in boiling mud and steam ejected several meters above the crater.…”
Section: Monitoring Of a Mud Volcano Fieldmentioning
confidence: 99%
“…Mud volcanoes are usually associated with quiet and continuous eruptions (Tingay, 2009), but sometimes they explode in dangerous and disruptive events. They are hazardous phenomena, because as of today, it is impossible to define the parameters for modelling the recurrence intervals of the extreme events (Gattuso et al, 2021). Azerbaijan hosts some mud volcanoes where the most violent eruptions worldwide are recorded; the Lökbatan mud volcano, for example, ex-plodes every 3-5 years in spectacular eruptions, which send detritus and breccia rafts into the Caspian Sea (Mazzini et al, 2021;Wang and Manga, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Some historically recorded explosive events occurred at the Salsa di Montegibbio (Sassuolo, Italy), the largest mud volcano in Italy (Borgatti et al, 2019), and were reported by Pliny the Elder (Naturalis Historia) in Roman times (50 CE) and later by Biasutti (1907), Govi (1906), and Stöhr (1867). Recently (2014), a sudden massive expulsion of fluids at the Macalube di Aragona mud volcano (Agrigento, Italy) caused the deaths of two children (Gattuso et al, 2021). Mud volcanoes, therefore, represent potential geohazards, especially where these features are located next to populated areas or where they are tourist destinations.…”
Section: Introductionmentioning
confidence: 99%